Facial tracking in video transfer using watershed segmentation - P, Mayilvahanan; S, Purushothaman; P, Rajeswari (International Journal of Engineering and Technology, 2014)
This paper presents the implementation of watershed segmentation for facial tracking. It focuses on tracking face of human in a continuous video transfer. The database is obtained from internet resource. Tracking efficiency is 97.2%.